CHRONIC INVERSION OF UTERUS - Begum, Nazakat; Faisal, Shaheen (Journal of Ayub Medical College Abbottabad, 1991)
The inversion of the uterus is a post-partum complication which is an obstetric emergency. The inversion of uterus may be acute, sub-acute and chronic inversion. The acute inversion is very rare and occurs in 1:20,000,00 to 1. 200.000 cases1. The causes of acute inversion of uterus are mismanagement of third stage of labour; e.g. trial of delivery of the placenta when the uterus is not yet involuted and placenta not yet separated, by pulling at the cord or by delivering it by Crude’s Method. It could also happen immediately after the delivery by sudden increase in intra-abdominal pressure, like coughing and sneezing2,3. If the acute inversion is missed at that time, and patient present later in puerperium, it is called chronic inversion. This is the most common cause of chronic inversion. Other causes of chronic inversion are fundal neoplasm and atrophic uterus.